Pengaruh Panic Buying, Kemudahan Cashless terhadap Perilaku Konsumtif pada Keluarga Muslim di Kota Medan - Yuannisa, Rizka Adlia; Nasution, Rizka; Batubara, Chuzaimah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
Currently, non-cash payment instruments are increasingly in demand because they make it easier for the public to make them more effective and efficient than using conventional payment instruments. Cashless society is a financial transaction by means of electronic payments in economic activities as a substitute for cash payments. A cashless society has the same goal in carrying out financial transactions using debit, credit or electronic methods that can be accessed via gadgets to make it easier for consumers. We can also feel the development of technology that continues to advance to facilitate people's lives in terms of transactions. This research uses quantitative methods. The results show that variable X, namely panic buying and cashless payments, has a significant effect on variable Y, namely the level of consumption. Keywords: panic buying, cashless payment, consumptive behaviour